Endogenous NO(3)(−) in the Root as a Source of Substrate for Reduction in the Light - Rufty, Thomas W. (1987)
An experiment was conducted to investigate the reduction of endogenous NO(3)(−), which had been taken up by plants in darkness, during the course of the subsequent light period. Vegetative, nonnodulated soybean plants (Glycine max [L]. Merrill, `Ransom') were exposed to 1.0 millimolar (15)NO(3)(−) for 12 hours in darkness and then returned to a solution containing 1.0 millimolar (14)NO(3)(−) for the 12 hours `chase' period in the light. Another set of plants was exposed to (15)NO(3)(−) during the light period to allow a direct comparison of contributions of substrate from the endogenous and exogenous sources. At the end of the (15)NO(3)(−) exposure in the dark, 70% of the absorbed (15)NO(3)(−) remained unreduced, and 83% of this unreduced NO(3)(−) was retained in roots. The pool of endogenous (15)NO(3)(−) in roots was depleted at a steady rate during the initial 9 hours of light and was utilized almost exclusively in the formation of insoluble reduced-N in leaves. Unlabeled endogenous NO(3)(−), which had accumulated in the root prior to the previous dark period, also was depleted in the light. When exogenous (15)NO(3)(−) was supplied during the light period, the rate of assimilation progressively increased, reflecting an increased rate of uptake and decreased accumulation of NO(3)(−) in the root tissue. The dark-absorbed endogenous NO(3)(−) in the root was the primary source of substrate for whole-plant NO(3)(−) reduction in the first 6 hours of the light period, and exogenous NO(3)(−) was the primary source of substrate thereafter. It is concluded that retention of NO(3)(−) in roots in darkness and its release in the following light period is an important whole-plant regulatory mechanism which serves to coordinate delivery of substrate with the maximal potential for NO(3)(−) assimilation in photosynthetic tissues.